2019
DOI: 10.1016/j.arabjc.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and antibacterial evaluation of epifriedelinol isolated from Vitex peduncularis Wall. ex Schauer

Abstract: Epifriedelinol, an antibacterial pentacyclic triterpene was isolated from the methanol extract of Vitex peduncularis by bio-assay guided separation and the structure of the compound was elucidated by various spectroscopic methods such as 1 H NMR, 13 C NMR and single crystal X-ray Diffraction. The antibacterial activity of epifriedelinol was examined against five species of Gram positive and seven strains of Gram negative bacteria. The presence of epifriedelinol in V. peduncularis and its antibacterial activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The isolated compounds were identified as friedelin ( 1 ), 3-β- friedelinol ( 2 ), epifriedelanol ( 3 ), euphol ( 4 ), cycloartenyl acetate ( 5 ), cycloartenol ( 6 ), epifriedelinyl acetate ( 7 ), and euphylbenzoate ( 8 ) using 1 H and 13 C NMR (see the Supporting Information). The structures of the isolated compounds were elucidated by comparison of their physical and spectral data ( 1 H and 13 C NMR) with those mentioned in the literature. …”
Section: Resultsmentioning
confidence: 99%
“…The isolated compounds were identified as friedelin ( 1 ), 3-β- friedelinol ( 2 ), epifriedelanol ( 3 ), euphol ( 4 ), cycloartenyl acetate ( 5 ), cycloartenol ( 6 ), epifriedelinyl acetate ( 7 ), and euphylbenzoate ( 8 ) using 1 H and 13 C NMR (see the Supporting Information). The structures of the isolated compounds were elucidated by comparison of their physical and spectral data ( 1 H and 13 C NMR) with those mentioned in the literature. …”
Section: Resultsmentioning
confidence: 99%
“…The 13 C‐NMR spectrum ( Figure 8) of the compounds 1 and 2 showed 32 carbon signals ( Table 2). The main chemical shifts referring to the presence of the compound 1 were: the signal at δ C 72.8 ppm (C‐3), indicative of the presence of carbinolic carbon; the signal at δ C 49.2 ppm, attributed to the methine carbon (C‐4); and the signal at δ C 11.6 ppm, which corresponds to the methyl group (C‐23) bonded to C‐4 [18] . The 1 H‐NMR spectrum ( Figure 9) for compound 1 showed a broad singlet at δ H 3.73 ppm, corresponding to hydrogen (H‐3) bonded to the carbinolic carbon, which is unshielded due to the electron‐withdrawing inductive effect exerted by oxygen atom.…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed with the pentacyclic triterpene epifriedelanol showed that the compound possesses antibacterial activity [18] . Friedelan‐3‐one exhibits antiproliferative, antioxidant, anti‐inflammatory, analgesic and antipyretic activities [31] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the secondary injury induced by TBI cannot be managed with existing drugs. Epifriedelinol (EFD), isolated from the roots of Aster tataricus [ 12 ], has strong anti-inflammatory, antibacterial, antioxidant, and anti-cancer effects [ 13 , 14 ]. This study evaluated the protective effects of EFD in TBI.…”
Section: Introductionmentioning
confidence: 99%